Mef2c is activated directly by Ets transcription factors through an evolutionarily conserved endothelial cell-specific enhancer. - De Val, S; Anderson, J; Heidt, AB; Khiem, D; Xu, S; Black, B (2004)
Members of the Myocyte Enhancer Factor 2 (MEF2) family of transcription factors play key roles in the development and differentiation of numerous cell types during mammalian development, including the vascular endothelium. Mef2c is expressed very early in the development of the endothelium, and genetic studies in mice have demonstrated that mef2c is required for vascular development. However, the transcriptional pathways involving MEF2C during endothelial cell development have not been defined. As a first step towards identifying the transcriptional factors upstream of MEF2C in the vascular endothelium, we screened for transcriptional enhancers from the mouse mef2c gene that regulate vascular expression in vivo. In this study, we identified a transcriptional enhancer from the mouse mef2c gene sufficient to direct expression to the vascular endothelium in transgenic embryos. This enhancer is active in endothelial cells within the developing vascular system from very early stages in vasculogenesis, and the enhancer remains robustly active in the vascular endothelium during embryogenesis and in adulthood. This mef2c endothelial cell enhancer contains four perfect consensus Ets transcription factor binding sites that are efficiently bound by Ets-1 protein in vitro and are required for enhancer function in transgenic embryos. Thus, these studies identify mef2c as a direct transcriptional target of Ets factors via an evolutionarily conserved transcriptional enhancer and establish a direct link between these two early regulators of vascular gene expression during endothelial cell development in vivo.